Politico everyman's guide to Philippine elections - XKQM Inc; Quantrumnet Systems, Inc (XKQM, 1998)
Produced by the Philippine Center for Investigative Journalism, this CD contains a discussion on the different stages of the Philippine electoral process; full text of election laws and related issuances, court decisions; [e.g.] procedures, election forms, facts and figures, proposed electoral reform laws, the vote count, automation program and a timetable of the Philippine political and electoral history